نفس مطمئنہ كے بارے امام رازی اور جمہور مفسرین كے اقوال كا جائزہ: An Analysis of Imam Razi’s and mainstream interpreters’ exegeses of Serene Soul (Khairulummah, 2023)
Imam R┐zi enjoys a celebrated position amongst the galaxy of scholars and is considered a master of all sciences of his time. His tafs┘r work Maf┐t┘╒ al Ghayb (The Keys to the unknown) is considered an encyclopedia in the field of Islamic studies generally and in the field of tafs┘r particularly. There is various interpretation of Serene Soul mentioned in Surah Al-Fajr, but Imam Razi deliberation of it is very clear and logical. On the other hand, mainstream interpreters’ some exegeses of serene soul is not logical, the reason is that many of them narrate from Tabari whose Tafsir is full of invalid points.  [1] - لیكچرار، شعبہ اسلامیات، جامعہ پشاور[2]   -     پی ایچ ڈی ریسرچ سكالر، شعبہ اسلامیات، جامعہ پشاور